The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1038/srep00842
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-mediated mRNA Translation Activation in Quiescent Cells and Oocytes Involves Recruitment of a Nuclear microRNP

Abstract: MicroRNAs can promote translation of specific mRNAs in quiescent (G0) mammalian cells and immature Xenopus laevis oocytes. We report that microRNA-mediated upregulation of target mRNAs in oocytes is dependent on nuclear entry of the microRNA; cytoplasmically-injected microRNA repress target mRNAs. Components of the activation microRNP, AGO, FXR1 (FXR1-iso-a) and miR16 are present in the nucleus and cytoplasm. Importantly, microRNA target mRNAs for upregulation, Myt1, TNFα and a reporter bearing the TNFα AU-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(139 citation statements)
references
References 59 publications
2
135
0
2
Order By: Relevance
“…29 In proliferating cells, FXR1a overexpression leads to microRNA mediated translation activation. 75 Consistently, proteomic studies in FXR1 depleted cells revealed decrease in protein levels of certain mRNAs that are targets of activation and require FXR1 for their polysome association. 31 Third, FXR1 does not interact with GW182 and does not lead to repression but instead promotes activation of translation.…”
Section: Critical Features Of Fxr1a-micrornp Mediated Translationmentioning
confidence: 68%
See 4 more Smart Citations
“…29 In proliferating cells, FXR1a overexpression leads to microRNA mediated translation activation. 75 Consistently, proteomic studies in FXR1 depleted cells revealed decrease in protein levels of certain mRNAs that are targets of activation and require FXR1 for their polysome association. 31 Third, FXR1 does not interact with GW182 and does not lead to repression but instead promotes activation of translation.…”
Section: Critical Features Of Fxr1a-micrornp Mediated Translationmentioning
confidence: 68%
“…25,31,75 Several intriguing questions emerge from these studies and remain to be addressed. First, it is not known how FXR1a-microRNP selects its targets for activation in G0.…”
Section: Future Questionsmentioning
confidence: 99%
See 3 more Smart Citations